Emerging Endoscopic Imaging Technologies for Bladder Cancer Detection - Lopez, Aristeo (2014)
Modern urologic endoscopy is the result of continuous innovations since early 19(th) century. White light cystoscopy is the primary strategy for identification, resection, and local staging of bladder cancer. While highly effective, white light cystoscopy has several well-recognized shortcomings. Recent advances in optical imaging technologies and device miniaturization hold the potential to improve bladder cancer diagnosis and resection. Photodynamic diagnosis and narrow band imaging are the first to enter the clinical arena. Confocal laser endomicroscopy, optical coherence tomography, Raman spectroscopy, UV autofluorescence, and others have shown promising clinical and pre-clinical feasibility. We review their mechanisms of action, highlight their respective advantages, and propose future directions.